How do Governments Fare about Redistribution? New Evidence on the Political Economy of Redistribution - Fabio Padovano; Francesco Scervini; Gilberto Turati (Center for Economic Studies and ifo Institute (CESifo), 2016)
We examine whether and to what extent political institutions explain different performances in income redistribution across countries. In particular, we first review available sources of data and measures of income redistribution, discussing the pros and cons of each one. Second, we outline a conceptual framework that distinguishes traditional demand side explanations of redistribution from resources and instruments, as well as supply side factors. We then provide empirical evidence on the association between these different factors and the observed degree of redistribution. Our analysis supports the view that – for a given demand of redistribution – political (and economic) institutions contribute to explain differences across countries in the observed degree of redistribution.
Keywords: D78; I38; H53; H11; 330; redistribution; ex ante and ex post Gini coefficients; political and economic institutions